Gender Instability in Maay - Paster, Mary (My University, 2018)
This paper discusses variation in the gender of nouns in Maay, a language of Somalia. Languages of the Eastern Omo-Tana subgroup of East Cushitic (including Maay, Somali, Rendille, and Tunni) have gender systems wherein every noun is masculine or feminine. Masculine nouns take k-initial variants of suffixes including the definite marker, demonstratives, and possessive markers; these suffixes are t-initial with feminine nouns. As is now well known, gender in these languages is sensitive to plurality in various ways: in some languages, gender ‘polarity’ reverses the gender of nouns in the plural; in others, feminine nouns change to masculine when their plurals are formed with certain suffixes but not others. In Maay, plurals are all masculine regardless of how they are formed, but the gender of many singular nouns is inconsistent across individuals. The masculine plural pattern makes the gender of singular nouns unrecoverable from their plurals, so nouns that are frequently plural are susceptible to gender instability. If there is uncertainty about the gender of some nouns, speakers may be inclined to guess masculine, thereby producing more feminine to masculine changes than the reverse, due to the prevalence of masculine nouns in the Maay lexicon.
Keywords: Gender instability; Maay; language; Somalia